PEMANFAATAN CANGKANG TELUR SEBAGAI PUPUK ORGANIK PADA TANAMAN KANGKUNG DARAT DI DESA NANOWA - Krisdayanti Maduwu (Jurnal Sapta Agrica, 2023)
Agriculture is a culture that was first developed by humans as a way for humans to maintain survival. This study aims to determine the Utilization of Egg Shells as Organic Fertilizer for Kangkung Darat in Nanowa Village. This type of research is a descriptive type of qualitative research. Data collection techniques used in this study are (1) Observation, (2) Interview. The data analysis technique in this study consists of three flow of activities that occur simultaneously, namely: (1) data reduction, (2) data presentation and (3) conclusion drawing/verification. Based on the results of the research and discussion obtained, there are several conclusions that can be drawn in this study as follows: (1) Good water spinach cultivation can get good productivity results (2) Egg shells have the potential to be used as organic fertilizer because they contain nutrients that are high in nutrients. plants need, such as calcium carbonate, potassium and phosphorus because these elements are very good for plant growth. Egg shells contain calcium carbonate and contain magnesium, sodium, potassium, zinc, manganese, iron and copper. (3) Utilization of egg shells on the growth of water spinach plants, has a very good impact or effect on the growth of land kale plants. Egg shells have the potential to be used as organic fertilizer because they contain nutrients needed by plants, such as calcium carbonate, potassium and phosphorus because these elements are very good for plant growth. Egg shells contain 97% calcium carbonate and an average of 3% phosphorus and 3% magnesium, sodium, potassium, zinc, manganese, iron and copper. The suggestion in the research is that farmers should be able to use egg shells as an alternative fertilizer for cultivating various plants, one of which is land kale.